Towards the professionalisation of public relations in Malaysia: perception management & strategy development. - Abdullah, Zulhamri; Threadgold, Terry (Elsevier Inc., 2008)
The aim of this study is to explore how the status and standards of public relations as a profession are perceived by the three main groups involved in public relations: academics, practitioners, and business leaders. It is concluded that public relations can be a ‘true’ profession if all parties involved are united and committed to developing standardised, universal forms of public relations practise.